Priming in response to pro-inflammatory cytokines is a feature of adult synovial but not dermal fibroblasts - Crowley, T; O’Neil, J; Adams, H; Thomas, A; Filer, A; Buckley, C; Clark, A (BioMed Central, 2017)
Background It has been hypothesized that chronic inflammatory diseases such as rheumatoid arthritis (RA) may be caused by a failure of negative feedback mechanisms. This study sought to examine negative feedback mechanisms in fibroblast-like synoviocytes (FLS), one of the most abundant cell types in the joint. We hypothesized that prior exposure of healthy FLS to an inflammatory stimulus would attenuate their responses to a second inflammatory stimulus, in the same way that negative feedback mechanisms desensitize macrophages to repeated stimulation by lipopolysaccharide. We further hypothesized that such negative feedback mechanisms would be defective in FLS derived from the joints in RA. Methods Synovial fibroblasts and dermal fibroblasts from non-inflamed joints and joints affected by RA and a fibroblast cell line from neonatal foreskin were stimulated twice with tumour necrosis factor (TNF) α or interleukin (IL)-1α, with a 24-h rest period between the two 24-h stimulations. Differences between response to the first and second dose of cytokine were examined by assessing secretion of inflammatory factors and intracellular signalling activity. Results FLS from both non-inflamed joints and joints affected by RA mounted an augmented response to re-stimulation. This response was site-specific, as primary dermal fibroblasts did not alter their response between doses. The fibroblast priming was also gene-specific and transient. Assessment of signalling events and nuclear localization showed prolonged activation of nuclear factor (NF)-κB during the second stimulation. Conclusion This study aimed to examine mechanisms of negative regulation of inflammatory responses in FLS. Instead, we found a pro-inflammatory stromal memory in FLS obtained from both non-inflamed joints and joints affected by RA. This suggests the joint is an area at high risk of chronic inflammation, and may provide a piece in the puzzle of how chronic inflammation is established in RA.